Keberhasilan Pemasaran Berkelanjutan dalam Bisnis: Pengaruh Kepemimpinan Inovatif dan Kolaboratif - Dodit Cahyo Nugroho; Titis Tatasari (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
The business sector faces increasingly complex market competition challenges, requiring marketing strategies that prioritize not only profit but also economic, social, and environmental sustainability. Innovative leadership and a collaborative culture are believed to play a crucial role in supporting sustainable marketing strategies. This study aims to analyze the relationship between innovative leadership, collaborative culture, and the success of sustainable marketing in businesses. The method used in this study was a questionnaire distributed to 100 business people. The questionnaires were then analyzed using multiple linear regression analysis. The results indicate that the more innovative leadership implemented, the higher the success of sustainable marketing strategies. Furthermore, the more collaborative leadership implemented, the greater the effectiveness and sustainability of marketing strategies. The study shows that there is limited literature directly linking innovative and collaborative leadership to sustainable marketing. However, the existing literature suggests that innovative leadership encourages creativity and strategic adaptation, while a collaborative culture strengthens team synergy and business networks, thus synergistically enhancing the success of sustainable marketing strategies. This research is expected to provide a theoretical basis for developing innovative and collaborative business management models with a sustainability orientation.